Pest, disease and chemical residues - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
ACP exports of fresh produce and fish face increasingly stringent checks in importing countries. In March alone risks highlighted included fruit imports to the EU from the southern hemisphere infected with fruit-fly larvae; fish from Kenva and...